Isiko Lehlathi 'The Customary Rights of the Forest': Unearthing the True Nature of Botanical Gardens - Ramodibe, Kekeletso (School of Architecture, Planning and Geomatics, 2023)
It is the apolitical position undertaken by Botanics such as Kirstenbosch Garden that further excludes people from engaging with Ihlathi through harvest and ritual. It prevents them from connecting with spaces that had once been occupied by their ancestors and still carry the consecrated nature of amasiko (customs). In reimagining these spaces with the understanding of African spirituality and indigenous contribution that has shaped Isiko Lehlathi (customary rites of the forest), the main goal is to re-enact the participatory activities, and interactions through design, which used to exist between people and nature. This is an attempt to break the colonial rigour to develop inclusive cultural principles of cultivation and harvest that share the same conservational values as the existing ones. Botanical Gardens have historically been defined by Eurocentric values of cultivating natural landscapes, conserving flora and fauna, and curating spaces that foster medicinal and educational studies of plants. However, they are often established in spaces that have immense cultural and consecrated significance such asehlathini (forest landscapes). South Africa is known as one of the most biodiverse countries in the world with a wide range of biomes, forests, deserts, estuaries, and aquatic systems (Biofin, 2021). These form part of a cultural ecology that is spiritually driven by amasiko (customs) of those who had created a sense of place from these landscapes. Botanical gardens such as Kirstenbosch are situated in forest landscapes that form part of the Capefloristic region protected areas. Conversely, it had been shaped by the existing legacy of colonization which is now sympatric to the traditional cultural rites of those who lived of these landscapes. This has continued to marginalize the history and heritage of Indigenous people such as the Khoi and San who have initiated a transcendent relationship with Ihlathi (forest landscapes).